Subjective Complaints of Respiratory Disorders Due to Silica Dust Exposure to Workers at PT Bumi Saran Beton Kalla Block - Alfina Baharuddin; Suharni A. Fachrin; Astrid Pratiwi Rufaedah Amir (Indian Journal of Forensic Medicine & Toxicology, 2021)
Purpose: The aims to analyze the effect of exposure to silica dust and individual characteristics on subjectivecomplaints of workers’Methods: The study design used a cross sectional approach. This research was conducted at PT. BumiSarana Beton Kalla Block, samples in this study were workers in the ballmill, mixing and packing as manyas 27 people using the total sampling method. Data analysis using chi-square test and multiple regressiontest.Results: the results showed that the effect of age on subjective complaints of respiratory disorders was p0.904> 0.05, the effect of smoking on subjective complaints of respiratory disorders p 0.485> 0.05, the effectof working tenure on subjective complaints of respiratory disorders p 0.728> 0.05, the effect of The use ofrespiratory protective equipment against subjective complaints of respiratory disorders p 0.820> 0.05, theeffect of work history on subjective complaints of respiratory disorders p 0.647> 0.05, the effect of exposureto silica dust on subjective complaints of respiratory disorders p 0.529> 0.05.Conclusion: exposure to silica dust and individual characteristic factors such as age, smoking habits, yearsof service, use of respiratory protective equipment, and work history are not significant to the subjectivecomplaints of respiratory